Modern features of a lecture in the format of distance learning for students of a medical university - Makurina, G. I.; Makarchuk, O. I.; Dmitrenko, I. P.; Golovkin, A. V.; Макуріна, Галина Іванівна; Макарчук, Олександр Іванович; Дмитренко, Інна Петрівна; Головкін, Анатолій Вячеславович; Макурина, Г. И.; Макарчук, А. И.; Дмитренко, И. П.; Головкин, А. В. (My University, 2021)
Modern conditions of life specify appropriate requirements to the training of medical specialists. Internet resources and on-line technologies become more popular in educational process. The objective of the work is to analyze the role of lectures in the educational process of students of a medical university on the basis of literature data, as well as to determine the features of the distance learning process at the Department of Dermatovenereology and Cosmetology with the Course of Aesthetic Medicine of FPE of Zaporizhzhia State Medical University. By means of analysis of scientific and pedagogical approaches to lecturing format in different countries two points of view can be defined. The first one is the classic notion about forms and methods of lecturing. Such point of view is typical for majority of educational institutions all over the world. But there is another point of view which emphasizes the fact that the passive transfer of material to students significantly decreases the educational level of specialists and therefore the introduction of new forms and methods for training of medical specialists is required. A special place in the preparation of students of medical universities should take an online lecture-visualization and a lecture-conference. It was in this format that lectures were introduced during quarantine in connection with the COVID- 19 pandemic at the Department of Dermatovenereology and Cosmetology with the Course of Aesthetic Medicine of FPE lectures were held using the MS Teams program based on Office 365 or Skype for business. During the lecture, the program provided for the possibility of interactive communication with groups of students or cadets. To control the effectiveness and perception of the information presented by the lecturer, an online questionnaire MS Forms on the topic of the lecture was used. The use of this software in lectures at the department helped to increase the level of cognitive processing of information, interest and motivation of all participants in the educational process. Современные условия жизни диктуют нам определенные требования к подготовке специалистов-медиков. Большую популярность набирают Интернет-ресурсы и онлайн технологии в образовательном процессе. Целью работы является анализ роли лекции в учебном процессе студентов медицинского ВУЗа на основании литературных данных, а также определение особенностей дистанционного учебного процесса на кафедре дерматовенерологии и косметологии с курсом дерматовенерологии и эстетической медицины ФПО ЗГМУ. Анализируя научно-педагогические подходы к формату проведения лекции в разных странах, можно выделить две точки зрения. Первая – это классическое представление о формах и методах проведения лекции. Такая точка зрения присуща большинству учебных заведений во всем мире. Но с другой стороны, пассивная передача материала студентам значительно снижает уровень подготовки специалистов и требует введения новых форм и методов подготовки студентов. Особое место в подготовке студентов медицинских ВУЗов должна занять онлайн лекция- визуализация и лекция-конференция. Именно в таком формате были введены лекции во время карантина в связи с пандемией CОVID-19 на кафедре дерматовенерологии и косметологии с курсом дерматовенерологии и эстетической медицины ФПО ЗГМУ. Чтение лекций проводилось с использованием программы MS Teams на базе Office 365 или Skype for business. В процессе проведения лекции программа предусматривала возможность интерактивного общения с группами студентов или курсантов. Для контроля результативности и восприятия изложенной лектором информации использовался онлайн-опросник МS Forms по теме лекции. Использование данного программного обеспечения в проведении лекций на базе кафедры способствовало повышению уровня когнитивной обработки информации, заинтересованности и мотивации всех участников учебно-воспитательного процесса.
Современные особенности проведения лекции в формате дистанционного обучения студентов медицинского ВУЗа
Keywords: distance learning; online media lecture; education; дистанционное обучение; онлайн медиа - лекция; образование